Neuropeptide W Attenuates Oxidative Multi-Organ Injury in Rats Induced with Intra-Abdominal Sepsis - YEGEN, BERRAK; ERCAN, FERİHA; AKKİPRİK, MUSTAFA (SPRINGER/PLENUM PUBLISHERS, 2022)
Sepsis leads to systemic hypotension, disturbed perfusion, inflammation, and tissue toxicity in vital organs. Neuropeptide W (NPW) has modulatory effects in the control of blood pressure and inflammatory processes, implicating a potential beneficial effect against sepsis-induced oxidative damage. Under anesthesia, male Sprague Dawley rats underwent cecal ligation and puncture. Immediately after surgery, either saline or TNF-alpha inhibitor (etanercept; 1 mg/kg) antibiotic (ceftriaxon; 10 mg/kg) combination or NPW (0.1, 1, or 3 mu g/kg) was given subcutaneously, and injections were repeated on the 12th and 24th h. The sham-operated control group was treated with saline at the same time points. All rats were euthanized on the 25th h of surgery. Sepsis resulted in oxidative damage of the brain, heart, lung, liver, and kidney. Elevations in blood urea nitrogen and alkaline phosphatase, showing renal and hepatic dysfunction, were not evident when septic rats were treated with NPW. NPW reduced serum levels of C-reactive protein, corticosterone, and interleukin-6, while histopathologically verified tissue damage in all the studied tissues was ameliorated. NPW treatment suppressed lipid peroxidation in the heart, lung, and brain, and the depleted antioxidant GSH levels of the brain and heart were replenished by NPW. Moreover, sepsis-related neutrophil recruitment to the liver and lung was also suppressed by NPW. Although the survival rate of the rats was not significantly prolonged by NPW, most of these improvements in systemic and local inflammatory events were comparable with those reached by the etanercept and antibiotic combination, suggesting the therapeutic impact of NPW during the acute period of sepsis.
Keywords: sepsis; oxidant injury; neuropeptide W; multi-organ damage; NF-KAPPA-B; ACUTE LUNG INJURY; INNATE IMMUNITY; CECAL LIGATION; ORGAN FAILURE; SEPTIC SHOCK; PROTEIN; RECEPTORS; PATHOGENESIS; ACTIVATION